PENGARUH PENGALAMAN KERJA DAN TINGKAT PENDIDIKAN TERHADAP KINERJA GURU SMP NEGERI I AROSBAYA KABUPATEN BANGKALAN YANG DI MEDIASI OLEH KEMAMPUAN KERJA - Nurul Qomariyah; Chamariyah Chamariyah; Subijanto Subijanto (Digital Bisnis: Jurnal Publikasi Ilmu Manajemen dan E-Commerce, 2022)
The results showed that: 1) Work experience had a significant positive effect on teacher performance with an original sample value of 0.244. 2) Work experience has a significant positive effect on work ability with the original sample value of 0.570. 3) Education level has a significant positive effect on work ability with the original sample value of 0.335. 4) Education level has a significant positive effect on teacher performance with the original sample value of 0.326. 5) Work ability has a significant positive effect on teacher performance with the original sample value of 0.417. 6) Work experience has a significant positive effect on teacher performance mediated by work ability with an original sample value of 0.238. 7) Education level has a significant positive effect on teacher performance mediated by work ability with the original sample value of 0.140.